2013
DOI: 10.1007/978-3-662-45758-0_252
|View full text |Cite
|
Sign up to set email alerts
|

A Systems Neuroscience Approach to the Pathophysiology of Pediatric Mood and Anxiety Disorders

Abstract: Emotional dysregulation is a core feature of pediatric mood and anxiety disorders. Emerging evidence suggests that these disorders are mediated by abnormalities in the functions and structures of the developing brain. This chapter reviews recent behavioral and functional magnetic resonance imaging (fMRI) research on pediatric mood and anxiety disorders, focusing on the neural mechanisms underlying these disorders. Throughout the chapter, we highlight the relationship between neural and behavioral findings, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 146 publications
(137 reference statements)
0
1
0
Order By: Relevance
“…Alterations in emotion-processing networks have been reported in studies in adolescents with anxiety or depression such as functional and structural changes in amygdalar and ACC networks. For example, impaired amygdala habituation and decreased ACC volume have been reported previously [5,6]. To our knowledge, few DTI studies in adolescents with clinical depression have been conducted.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Alterations in emotion-processing networks have been reported in studies in adolescents with anxiety or depression such as functional and structural changes in amygdalar and ACC networks. For example, impaired amygdala habituation and decreased ACC volume have been reported previously [5,6]. To our knowledge, few DTI studies in adolescents with clinical depression have been conducted.…”
Section: Introductionmentioning
confidence: 88%
“…The UF, corpus callosum, IFOF and cingulum are thought to be involved in regulation and communication within and between regions of the corticolimbic network [12,13]. Interestingly, these results seem to show overlapping patterns compared to adult depression and anxiety, although studies in the adolescent population are still few (Strawn et al, 2014;Tseng et al, 2014). Considering the above, alterations in functional and structural regions involved in the corticolimbic network are likely to play a role in adolescent anxiety and depression and could be targets for further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…, 21 Moreover, these difficulties have been found to predict the early onset 22 and the recurrence 23 , 24 of mood episodes, which suggests that impairments in specific domains of emotional functioning reflect stable vulnerabilities that place individuals at increased risk for experiencing recurrent mood episodes. Neuroimaging and other studies in pursuit of biomarkers of mood disorders have complemented these clinical findings, 25 and have documented aberrant structure, function, and connectivity in brain regions that subserve these aspects of emotion and emotional regulation, 26 along with key molecular (eg, mitochondrial dysfunction) and genetic vulnerabilities for mood symptoms in youth 27 . Specifically, investigators have reported structural anomalies in pediatric mood disorders in the amygdala and hippocampus, and functional abnormalities in the ventrolateral (VLPFC) and dorsolateral prefrontal cortex (DLPFC), amygdala, and ventral striatum 28 .…”
Section: Introductionmentioning
confidence: 99%